382 Clinical manifestation and prognosis of different cardiomyopathies on the base of genetic background (GEN-PHEN). (8th December 2021) - Paldino, Alessia; Stolfo, Davide; Dal Ferro, Matteo; Gigli, Marta; Medo, Kristen; Graw, Sharon; Gagno, Giulia; Zaffalon, Denise; Gandin, Ilaria; Taylor, Matthew; Masè, Marco; Merlo, Marco; et al.
Abstract: Aims: Cardiomyopathies (CMP) are a heterogeneous group of heart disease characterized by structural and electrical abnormalities with no other secondary causative etiology and frequently related to mutations in disease related genes. Clinical evaluation and phenotype definition are the key factors for clinical classification of CMPs. Recent studies in this field have showed important phenotype overlaps between Dilated Cardiomyopathy (DCM) and Arrhythmogenic Cardiomyopathy (ACM), making the diagnosis a challenging task. The aim of this study is to assess whether a classification of CMP patients (not hypertrophic) based on genetic characterization outperforms in diagnostic and prognostic accuracy the classical, phenotype-driven, diagnostic approach. Methods and results: We analysed a population of patients affected by genetically determined DCM and ACM, carriers of 'pathogenic' or 'likely pathogenic' (P/LP) variants, registered into the Heart Disease Centers of Trieste and Denver hospitals. First, we described the phenotype distribution in our population with a clinical and echocardiographic evaluation based on the different disease-related mutated genes. Then, we examined the prognostic impact of the single gene/genetic cluster in assessing these composite outcomes: (1) all-cause mortality and heart transplant; (2) heart failure-related death, heart transplant or destination left ventricular assist device implantation (DHF/HTx/VAD); and (3) sudden cardiac death, sustained ventricular tachycardia/ventricular fibrillation or appropriate defibrillator shock (SCD/VT/VF/shock). 281 patients carrying P/LP variants (82% DCM) were included in the study. Titin (TTN) and sarcomeric genes (SARC) variants were the most prevalent (TTN: 95 patients, 34% of total population; SARC: 63 patients, 22% of total population) and almost completely related to DCM phenotype (TTN: 100% DCM, SARC: 95% DCM), such as lamin (LMNA) patients (29 patients, 10% of total population, 96% DCM). A more heterogeneous phenotypic distribution between DCM and ACM were detected for desmoplakin (DSP), plakoglobin (PKP2), and filamin (FLNC) variants. Patients with not isolated DCM phenotype and patients' carriers of DSP, PKP2, FLNC and LMNA variants (arrhythmic genes) experienced more frequent SCD/VT/VF/shock events ( P -value = 0.002 and P  = 0.023), compared respectively to patients with DCM phenotype and to patients' carriers of TTNtv and SARC variants, during follow-up (median time 132 months). The multivariable analysis shown that only P/LP variants of arrhythmic genes, younger age of disease onset and male gender, were associated with an increased risk of SCD/VT/VF/shock events during follow-up. No difference in terms of HF events was significantly related to genotype. Conclusions: Our study demonstrated that the classification based on the presence of a specific genotype outperforms phenotypic classification in terms of arrhythmic risk in a large DCM and ACM population with a positive genetic test for P/LP variants. These findings support the need of extensive genetic testing to support CMP diagnosis and prognosis.